Undrained shear strength of soft clay reinforced with 6mm and 8mm diameter group of bottom ash column - Nurul Fauziana, Abu Bakar (2014)
This study is to determine the undrained shear strength of the soft clay reinforced with the bottom ash column. The coal combustion products are generated from the coal combustion process in order to produce electricity. The coal combustion product consists of fly ash, bottom ash, boiler slag and flue gas desulflirizatjon (FGD) material. This coal combustion product is disposed in the landfill, if this situation continued it will utilize lots of space. By reusing the waste or by product bottom ash as a raw material in the construction, the usage of the non-renewable natural material such as aggregate can be reduced.The angular shape of the bottom ash particle is similar to the aggregate shape, the angular shape is important in order to obtain a strong bond between the materials in the construction. Soft clay is known as the problematic soil because of the weakness in strength characteristic and high compressibility. Due to the soft clay characteristic the ground improvement needs to be conducted in order to increase and improve the soft clay strength. Stone columns are one of the ground improvement methods that usually been conducted toward the soft clay.There are several advantages that can be obtain by using the stone column as the ground improvement method such as the soil bearing capacity can be increased, the total and differential settlements can be minimize and accelerates the consolidation settlement. Sustainable construction also known as the green construction, it is an action which aims to reduce the environmental impact of the construction over its entire lifetime, at the same time it has to be safe and comforts toward its occupants. The sustainable constructions are the development that meets the need of the present without compromising the environmental aspects for the future generation. By reuse, reduce and recycle the sustainability in construction can be achieve. The aim of this study is to investigate the improvement of undrained shear strength of soft clay reinforced with the group bottom ash column in which the physical characteristic and mechanical characteristic of kaolin clay and bottom ash are determined. The undrained shear strength parameter of soft clay and soft clay reinforced with various dimensions of the group bottom ash column are compare to determine whether there is any increment after the insertion of the bottom ash column. Correlations relating the undrained shear strength parameter with various dimensions of the group bottom ash column installed in soft clay are established. Based on the results that been obtained from this study indicate that the shear strength of the soft clay reinforced with bottom ash column are improved.